2017
DOI: 10.1007/s12640-017-9810-1
|View full text |Cite
|
Sign up to set email alerts
|

NMDA Receptors and NO:cGMP Signaling Pathway Mediate the Diazepam-Induced Sensitization to Withdrawal Signs in Mice

Abstract: The goal of the present study was to examine the effects of N-methyl—aspartate (NMDA) receptor antagonists—memantine and ketamine and the drugs modifying the NO:cGMP pathway—NG-nitro-L-arginine methyl ester (L-NAME) and 7-nitroindazole (7-NI), the endogenous precursor of NO-L-arginine, and the guanylyl cyclase inhibitor—methylene blue (MB) on the development of sensitization to withdrawal signs precipitated after chronic, interrupted treatment with diazepam, a benzodiazepine receptor agonist, in mice. To devel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
12
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 56 publications
(71 reference statements)
1
12
0
Order By: Relevance
“…Clinical widely used medicines such as fluoxetine, imipramine [44], and venlafaxine [35] were also reported to enhance the antidepressant-like effect with 7-NI. Our results demonstrated that ineffective YJ could decrease the immobility time in mice with 7-nitroindazole and MB treatment, which was consistent with other researches [52–54].…”
Section: Discussionsupporting
confidence: 93%
“…Clinical widely used medicines such as fluoxetine, imipramine [44], and venlafaxine [35] were also reported to enhance the antidepressant-like effect with 7-NI. Our results demonstrated that ineffective YJ could decrease the immobility time in mice with 7-nitroindazole and MB treatment, which was consistent with other researches [52–54].…”
Section: Discussionsupporting
confidence: 93%
“…Among the most effective classic tranquilizers -derivatives of benzodiazepine used in the treatment of anxiety pathologies, diazepam stands out. However, it has side effects on the behavioral component -fatigue and lack of emotions or, on the contrary, acute agitation, anxiety, hallucinations and fits of rage (Talarek et al 2018). The group of "daytime" sedatives has milder unwanted actions, but even their use can result in increased irritability, psychomotor agitation, confusion (tofisopam), sedation, drowsiness, fatigue and a slow-down in reactivity (medazepam).…”
Section: Resultsmentioning
confidence: 99%
“…In our previous studies, we demonstrated that the tested substances affecting the L-arginine-NO-cGMP-dependent pathway do not influence the spontaneous locomotor activity of male albino Swiss mice when given alone at the doses used in the current experiment. [59][60][61][62] Therefore, the observed effects could not have been noted because of disturbed locomotor activity of mice exerted by the tested agents. Similarly to the outcomes of our study, 7-nitroindazole blocked the expression of psychomotor sensitization produced by methamphetamine, 36 3,4-methylenedioxymethamphetamine, 33 methylphenidate 37 and cocaine, 38 whereas L-NAME inhibited the expression of sensitization produced by amphetamine 35 and morphine.…”
Section: Discussionmentioning
confidence: 99%
“…To check whether the L-arginine-NO-cGMP-dependent pathway previous experiments performed in our lab. 24,59,61,62 Locomotor activity of animals was measured in actimeter cages (Multiserv). On the 1st, 5th and 20th day of the experiment, just after the mephedrone or saline injection, a given mouse was placed individually into the cage and its locomotion was measured for 10, 30 and 60 min.…”
Section: Expression Of Sensitization To the Mephedrone-induced Hyperl...mentioning
confidence: 99%